Demonstrating gain in a dielectric Cherenkov maser with a rod slow-wave system - Avgustinovich V. A. Vladimir Andreevich; Artemenko S. N. Sergey Nikolaevich; Mashchenko A. I. Aleksandr Ivanovich; Shlapakovskii A. S.; Yushkov Y. G. Yuri Georgievich (2010, 2010)
Title screen